IMP1 regulates UCA1-mediated cell invasion through facilitating UCA1 decay and decreasing the sponge effect of UCA1 for miR-122-5p - Zhou, Yanchun; Meng, Xiuhua; Chen, Shaoying; Li, Wei; Li, Delin; Singer, Robert; Gu, Wei (Breast cancer research : BCR, 2018)
Long noncoding RNAs (LncRNAs) represent a class of widespread and diverse endogenous RNAs that can posttranscriptionally regulate gene expression through the interaction with RNA-binding proteins and micro RNAs (miRNAs). Here, we report that in breast carcinoma cells, the insulin-like growth factor 2 messenger RNA binding protein (IMP1) binds to lncRNA urethral carcinoma-associated 1 (UCA1) and suppresses the UCA1-induced invasive phenotype. RT-qPCR and RNA sequence assays were used to investigate the expression of UCA1 and miRNAs in breast cancer cells in response to IMP1 expression. The role of IMP1-UCA1 interaction in cell invasion was demonstrated by transwell analysis through loss-of-function and gain-of-function effects. RNA pull-down and RNA binding protein immunoprecipitation (RIP) were performed to confirm the molecular interactions of IMP1-UCA1 and UCA1-miR-122-5p involved in breast cancer cells. In breast cancer cells, IMP1 interacts with UCA1 via the "ACACCC" motifs within UCA1 and destabilizes UCA1 through the recruitment of CCR4-NOT1 deadenylase complex. Meanwhile, binding of IMP1 prevents the association of miR-122-5p with UCA1, thereby shifting the availability of miR-122-5p from UCA1 to the target mRNAs and reducing the UCA1-mediated cell invasion. Accordingly, either IMP1 silencing or UCA1 overexpression resulted in reduced levels of free miR-122-5p within the cytoplasm, affecting miR-122-5p in regulating its target mRNAs. Our study provides initial evidence that interaction between IMP1 and UCA1 enhances UCA1 decay and competes for miR-122-5p binding, leading to the liberation of miR-122-5p activity and the reduction of cell invasiveness.